The Fish-Specific Protein Kinase (PKZ) Initiates Innate Immune Responses via IRF3- and ISGF3-Like Mediated Pathways - Xu, Xiaowen; Li, Meifeng; Wu, Chuxin; Li, Dongming; Jiang, Zeyin; Liu, Changxin; Cheng, Bo; Mao, Huiling; Hu, Chengyu (Frontiers in Immunology, 2019)
PKZ is a fish-specific protein kinase containing Zα domains. PKZ is known to induce apoptosis through phosphorylating eukaryotic initiation factor 2α kinase (eIF2α) in the same way as double-stranded RNA-dependent protein kinase (PKR), but its exact role in detecting pathogens remains to be fully elucidated. Herein, we have found that PKZ acts as a fish-specific DNA sensor by initiating IFN expression through IRF3- or ISGF3-like mediated pathways. The expression pattern of PKZ is similar to those of innate immunity mediators stimulated by poly (dA:dT) and poly (dG:dC). DNA-PKZ interaction can enhance PKZ phosphorylation and dimerization in vitro. These findings indicate that PKZ participates in cytoplasmic DNA-mediated signaling. Subcellular localization assays have also shown that PKZ is located in the cytoplasm, which suggests that PKZ acts as a cytoplasmic PRR. Meanwhile, co-IP assays have shown that PKZ can separately interact with IRF3, STING, ZDHHC1, eIF2α, IRF9, and STAT2. Further investigations have revealed that PKZ can activate IRF3 and STAT2; and that IRF3-dependent and ISGF3-like dependent mediators are critical for PKZ-induced IFN expression. These results demonstrate that PKZ acts as a special DNA pattern-recognition receptor, and that PKZ can trigger immune responses through IRF3-mediated or ISGF3-like mediated pathways in fish.